The Influence of obesity on developing osteoarthritis and the recovery after knee joint replacement - a review - Karolina Pasieka; Helena Perenc; Karolina Majka; Kornelia Krawczyk; Marek Pędras; Michał Kosar; Paulina Kosiorowska; Urszula Korzonek; Kuba Kupniewski (Nicolaus Copernicus University in Toruń, 2024)
Obesity is a chronic disease accompanied by inflammation. It is becoming more and more prevalent all around the world and so are its consequences. Osteoarthritis (OA) is a degenerative disease of the joints. The range of its risk factors is broad, but the most common is obesity. OA can be treated in a surgical and non-surgical way. The surgical method - knee replacement is the most effective way of treating OA, but unfortunately it does not solve the problem. Obesity takes a part not only in development of OA, but is also involved in developing postoperative complications and impairing the recovery in general. The influence of obesity is determined not only by the weight and increased mechanical forces affecting the organism, but also on a molecular level by the hormonal activity of the substances produced by white adipose tissue. Condition of the patient should be optimised before the surgery in order to minimize the risk of complications and increase the chances for fast and effective recovery. Obese patients after the surgery need proper nutrition and care focused on their needs, which often is a challenge to the healthcare providers. After the surgery those patients cannot be sent back to the condition that made them sick. Reduction of weight is suggested to prevent the development of postoperative complications and OA. Prehabilitation seems to improve the immediate postoperative results. Starting regular training a few weeks after the surgery seems to positively affect the process of recovery.